Membaca Dan Memaknai Mazmur Ratapan 12 Dengan Metode Baca Gali Alkitab - Hasahatan Hutahaean; Elirani Gea; Adarsan Simarmata (Manna Rafflesia, 2020)
One type of psalm is Lament. Psalms of Lament sung with weeping, weeping driven by the psalmist's sorrow. David wrote many psalms where one of them is lamentation in Psalm 12. In this article the psalmist experienced a change of mood (feeling) from lamenting, joyful hope then again lamenting. The research in this paper used a qualitative approach to library research methods. Literature research requires a study of related literature to guide researchers to achieve the research objectives of the data taken based on selected books. While the interpretation to find the meaning of the text of the Research Team uses the method of Reading the Bible (BGA). The methods of BGA are simple but practice interpretation that was designed initially for Christian quiet times. After Psalm 12 interpreted, the Research Team founded that the psalmist was still lamenting over the situation around him. Even though the psalmist experienced joy because God will save, but the wicked are still there and rottenness still arises among the sons of men. Because God works not based on the presence or absence of the wicked and rottenness among the children of men.